2011
DOI: 10.1017/s1355617711000981
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Visual Scanning and Memory for Faces in High-Functioning Autism Spectrum Disorders: It's Not Just the Eyes

Abstract: Prior studies suggest that autism spectrum disorders (ASD) are associated with a domain-specific memory impairment for faces. The underlying cause of this problem and its relation to impaired visual scanning of faces—particularly of the eyes—remains to be determined. We recorded eye movements while 22 high-functioning ASD and 21 typically developing (TD) adolescents encoded and later recognized faces and objects from a single, nonsocial object category (electric fans). Relative to TD subjects, ASD individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 29 publications
3
42
2
Order By: Relevance
“…Deficits are most often noted in the presence of memory demands (Weigelt, Koldewyn, & Kanwisher, 2012), and evidence of intact memory for non-face images such as patterns, buildings, and electric fans implies a face-specific deficit rather than a domain-general impairment (Boucher & Lewis, 1992; McPartland, Webb, Keehn, & Dawson, 2011; Snow et al, 2011; Weigelt, Koldewyn, & Kanwisher, 2012). Further disruption is found in tasks utilizing face discrimination (Deruelle, Rondan, Gepner, & Tardif, 2004; Gepner, de Gelder, & de Schonen, 2007; Tantam, Monaghan, Nicholson, & Stirling, 1989) and lip reading, gender and gaze discrimination (Deruelle et al, 2004).…”
Section: Childhoodmentioning
confidence: 99%
“…Deficits are most often noted in the presence of memory demands (Weigelt, Koldewyn, & Kanwisher, 2012), and evidence of intact memory for non-face images such as patterns, buildings, and electric fans implies a face-specific deficit rather than a domain-general impairment (Boucher & Lewis, 1992; McPartland, Webb, Keehn, & Dawson, 2011; Snow et al, 2011; Weigelt, Koldewyn, & Kanwisher, 2012). Further disruption is found in tasks utilizing face discrimination (Deruelle, Rondan, Gepner, & Tardif, 2004; Gepner, de Gelder, & de Schonen, 2007; Tantam, Monaghan, Nicholson, & Stirling, 1989) and lip reading, gender and gaze discrimination (Deruelle et al, 2004).…”
Section: Childhoodmentioning
confidence: 99%
“…Deviations from characteristic spatial or temporal eye-movement patterns to faces have been shown to reflect disorders including autism spectrum disorders (Kliemann, Dziobek, Hatri, Steimke, & Heekeren, 2010; Klin, Jones, Schultz, Volkmar, & Cohen, 2002; Morris, Pelphrey, & McCarthy, 2007; Pelphrey et al, 2002; Pelphrey, Morris, & McCarthy, 2005; Snow et al, 2011), schizophrenia (Green, Williams, & Davidson, 2003a, 2003b; Manor et al, 1999; M L Phillips & David, 1997; Mary L. Phillips & David, 1997, 1998; Streit, Wölwer, & Gaebel, 1997; Williams, Loughland, Gordon, & Davidson, 1999), bipolar disorder (Bestelmeyer et al, 2006; E. Kim et al, 2009; P.…”
Section: - Introductionmentioning
confidence: 99%
“…In a recent review, we identified sixteen studies comparing face identity recognition (henceforth referred to as “face recognition) to the recognition of other visual objects in ASD, as needed to test the domain specificity of the deficit. Twelve of these studies report domain-selective deficits in which face recognition was more impaired than recognition of visual patterns [2][4], cars [5], [6], buildings [5][8], Greebles [9], common objects [9], shoes [10][12] and fans [13]. One additional study of 12 adults with ASD found that they performed worse than age-and IQ-matched adults with learning disabilities on memory for faces, but performed at least as well on memory for cats, horses, motorbikes, leaves and buildings [14] (That study also tested a group of adults that were age, but not IQ-matched to the group of adults with ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent review [1] found that deficits in face recognition in ASD are more often reported in studies with a high memory demand (face memory studies; [4], [7], [13]) than in studies with little or no memory demand (face perception studies; [19], [20]). One study used both a face memory and a face perception task on the same participants, and found that face recognition was more impaired when the faces had to be remembered over a delay than when they did not [10].…”
Section: Introductionmentioning
confidence: 99%